Sharia Compliance, Social Performance, and Financial Performance: A Study on Indonesian Rural Islamic Banks - Nurkhin, Ahmad; Mukhibad, Hasan; Hapsoro, Bayu Bagas; Kusumantoro, Kusumantoro; Nugroho, Rosyid Wahyu; Nor, Fakhrudin; Daud, Norzaidi Mohd (LPPM ISNJ Bengkalis, 2025)
Purpose – The indicator of Sharia compliance is the social performance that the rural Islamic bank must realize by distributing zakat, infaq, and alms funds to those in need. This study analyzes the relationship between rural Islamic banks' social performance, bank-specific characteristics, and financial performance in Indonesia during 2020-2023. Method – The study uses descriptive and panel data regression analyses from 97 rural Islamic banks registered with the Financial Services Authority (Otoritas Jasa Keuangan or OJK). The data collection method used is documentation. The data analysis technique used is descriptive and multiple regression analysis of panel data. Findings – The study's results indicate a significant and positive effect of social performance on financial performance as measured by return on assets (ROA). The level of Non-Performing Financing (NPF) has a negative and significant effect on ROA. Bank size has also been proven to significantly and positively impact ROA. Other results indicate that specific bank characteristics such as capital adequacy ratio (CAR), productive asset quality, financing deposit ratio (FDR), and cash ratio cannot significantly determine the ROA level. Implications – Social performance is part of promoting sustainable performance that supports achieving sustainable development goals (SDGs). Rural Islamic banks should also significantly impact social and environmental issues, especially zakat performance.